Antibody-mediated rejection of arterialised venous allografts is inhibited by immunosuppression in rats - Splith, Katrin; Fellmer, Peter; Matia, Ivan; Varga, Martin; Oliverius, Martin; Kuhn, Stephanie; Feldbrügge, Linda; Krenzien, Felix; Hau, Hans-Michael; Wiltberger, Georg; Schmelzle, Moritz; Jonas, Sven (PloS one, 2014)
OBJECTIVES AND DESIGN: We determined in a rat model (1) the presence and dynamics of alloantibodies recognizing MHC complexes on quiescent Brown-Norway (BN) splenic cells in the sera of Lewis (LEW) recipients of Brown-Norway iliolumbar vein grafts under tacrolimus immunosuppression; and (2) the presence of immunoglobulins in the wall of acute rejected vein allografts. MATERIALS AND METHODS: Flow cytometry was used for the analysis of day 0, 14 and 30 sera obtained from Lewis recipients of isogeneic iliolumbar vein grafts (group A) or Brown-Norway grafts (group B, C) for the presence of donor specific anti-MHC class I and II antibodies. Tacrolimus 0.2 mg/kg daily was administered from day 1 to day 30 (group C). Histology was performed on day 30. RESULTS: Sera obtained preoperatively and on day 30 were compared in all groups. The statistically significant decrease of anti MHC class I and II antibody binding was observed only in allogenic non-immunosuppressed group B (splenocytes: MHC class I - day 0 (93% ± 7% ) vs day 30 (66% ± 7%), p = 0.02, MHC class II - day 0 (105% ± 3% ) vs day 30 (83% ± 5%), p = 0.003; B-cells: MHC class I - day 0 (83% ± 5%) vs day 30 (55% ± 6%), p = 0.003, MHC class II - day 0 (101% ± 1%) vs day 30 (79% ± 6%), p = 0.006; T-cells: MHC class I - day 0 (71% ± 7%) vs day 30 (49% ± 5%), p = 0.04). No free clusters of immunoglobulin G deposition were detected in any experimental group. CONCLUSION: Arterialized venous allografts induce strong donor-specific anti-MHC class I and anti-MHC class II antibody production with subsequent immune-mediated destruction of these allografts with no evidence of immunoglobulin G deposition. Low-dose tacrolimus suppress the donor-specific antibody production.
Keywords: Histocompatibility Antigens Class I; Veins; Graft Rejection; Transplantation Immunology; podskupiny lymfocytů; krysa rodu Rattus; transplantační imunologie; alografty; zvířata; imunosupresivní léčba; časové faktory; Isoantibodies; arterie; Arteries; Lymphocyte Subsets; Male; Spleen; Immunosuppression Therapy; buněčná cytotoxicita závislá na protilátkách; Antibody-Dependent Cell Cytotoxicity; vény; Rats; Allografts; Animals; Histocompatibility Antigens Class II; MHC antigeny I. třídy; MHC antigeny II. třídy; mužské pohlaví; Time Factors; rejekce štěpu; isoprotilátky; slezina